2008
DOI: 10.1111/j.1365-2710.2008.00912.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistence with hepatitis C therapy in the Department of Veterans Affairs

Abstract: Peg alfa-2A/Rib showed slightly higher persistence rates for the overall duration of treatment as compared to Peg alfa-2B/Rib. However the differences, even though statistically significant, are small and not likely to translate into any substantial clinical advantage. Further research involving other approaches is required to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
2
2
0
Order By: Relevance
“…Although comparisons to other studies are difficult because of differences in methodology, the mean treatment duration of 215 days is consistent with estimates from other studies of 172–240 days [ 15 , 16 , 19 , 30 ]. In a retrospective cohort study of Veterans Affairs patients, two of the most common TECs we identified, anemia and neutropenia, were associated with lower persistence with PEG-IFN-alfa/ribavirin treatment (mean 172 days) [ 30 ]. Similar to patients in our study, the investigators identified patients with anemia and neutropenia through both ICD-9-CM codes and by identifying medication use (specifically the use of growth factors).…”
Section: Discussionsupporting
confidence: 84%
“…Although comparisons to other studies are difficult because of differences in methodology, the mean treatment duration of 215 days is consistent with estimates from other studies of 172–240 days [ 15 , 16 , 19 , 30 ]. In a retrospective cohort study of Veterans Affairs patients, two of the most common TECs we identified, anemia and neutropenia, were associated with lower persistence with PEG-IFN-alfa/ribavirin treatment (mean 172 days) [ 30 ]. Similar to patients in our study, the investigators identified patients with anemia and neutropenia through both ICD-9-CM codes and by identifying medication use (specifically the use of growth factors).…”
Section: Discussionsupporting
confidence: 84%
“…20,21 However, the difference in persistence rates observed between the two agents may not translate into any meaningful differences in clinical outcomes. 30 The results of the current analysis are in accord with those from the VA study, 30 as persistence rates were likely to be higher with peginterferon alfa-2a than with peginterferon alfa2b; however, further trials and studies Table 3. are required to explore whether such persistence differences have clinical significance.…”
Section: Discussionsupporting
confidence: 85%
“…30 It is possible that the higher persistence rates observed with peginterferon alfa-2a versus peginterferon alfa-2b may be attributable to the differences in the pharmacokinetic and tolerability profiles between the agents. In fact, higher treatment discontinuation rates have been observed with peginterferon alfa-2b than with peginterferon alfa-2a.…”
Section: Discussionmentioning
confidence: 98%
“…In a regional cohort of veterans undergoing substance abuse treatment, early discontinuation estimates were 60% among G1/4 patients and 27-32% among G2/3 patients [15]. In two U.S. cohorts of primarily genotype 1-infected veterans treated with interferon or Peg-IFN, more than 75% failed to complete 48 weeks of treatment [16,17], though discontinuers are not distinguished by their reason for discontinuation. Backus et al report cumulative days’ supply instead of weeks on treatment for genotype 1-, 2-, and 3-infected veterans; 43% of genotype 1 patients, 30% of genotype 2 patients, and 25% of genotype 3 patients did not have 100% cumulative days’ supply [18].…”
Section: Discussionmentioning
confidence: 99%